The evolution of HIV policy in Vietnam: from punitive control measures to a more rights-based approach - Pham Nguyen Ha; Anastasia Pharris; Nguyen Thanh Huong; Nguyen Thi Kim Chuc; Ruairi Brugha; Anna Thorson (Taylor & Francis Group, 2010)
Aim: Policymaking in Vietnam has traditionally been the preserve of the political elite, not open to the scrutiny of those outside the Communist Party. This paper aims to analyse Vietnam's HIV policy development in order to describe and understand the policy content, policy-making processes, actors and obstacles to policy implementation. Methods: Nine policy documents on HIV were analysed and 17 key informant interviews were conducted in Hanoi and Quang Ninh Province, based on a predesigned interview guide. Framework analysis, a type of qualitative content analysis, was applied for data analysis. Results: Our main finding was that during the last two decades, developments in HIV policy in Vietnam were driven in a top-down way by the state organs, with support and resources coming from international agencies. Four major themes were identified: HIV policy content, the policy-making processes, the actors involved and human resources for policy implementation. Vietnam's HIV policy has evolved from one focused on punitive control measures to a more rights-based approach, encompassing harm reduction and payment of health insurance for medical costs of patients with HIV-related illness. Low salaries and staff reluctance to work with patients, many of whom are drug users and female sex workers, were described as the main barriers to low health staff motivation. Conclusion: Health policy analysis approaches can be applied in a traditional one party state and can demonstrate how similar policy changes take place, as those found in pluralistic societies, but through more top-down and somewhat hidden processes. Enhanced participation of other actors, like civil society in the policy process, is likely to contribute to policy formulation and implementation that meets the diverse needs and concerns of its population.